The Unintended Effects of Director and Officer Liability Protection on Corporate Tax Avoidance: A Review of the Literature - Yessica Amelia; Muhammad Rizal; Farah Qalbia (LPPM STIE Kasih Bangsa, 2025)
This qualitative literature review investigates the unintended consequences of director and officer (D&O) liability protection on corporate tax avoidance. By examining relevant studies, the review reveals that D&O liability protection can inadvertently foster aggressive tax avoidance behaviors due to the moral hazard it creates for executives. While these protections aim to shield executives from personal financial risks, they may unintentionally encourage risky tax strategies that prioritize short-term gains over long-term corporate sustainability. The findings highlight the importance of strong corporate governance and regulatory reforms to mitigate such consequences. This review contributes to understanding the complex relationship between D&O liability protection and corporate tax avoidance, emphasizing the need for more effective oversight and policies to align executive decision-making with broader public and corporate interests.